Playful Innovating Pedagogy for Entrepreneurial Learning - Heljakka, Katriina; Kangas, Marjaana; Legaard, Jesper Falck (United States, 2026)
his study introduces a pedagogical framework for playful entrepreneurial learning that can be utilized in Higher Education (HE) and, more broadly, innovative education and research. Through a multidisciplinary teaching innovation focusing on rapid prototyping and crafting of toys, an international group of teachers interested in the capacities of playful learning (PL) conducted a playful learning session first with entrepreneurship students and second with teaching education students in Finland. Building on previous theories of PL, the framework presented includes various learning tools, both tangible and technological. The playful pedagogy is grounded in sociocultural, socio-material, and enactivist approaches aimed to facilitate an entrepreneurial mindset as part of toy design assisted by everyday materials with the idea of constructing three-dimensional toy-like or playable objects as part of group work. The students were also allowed to use AI. The findings illustrate that in the emerging AI era, HE students benefit from engaging with simple materials to complement advanced technological tools such as generative AI. Our study shows that entrepreneurial learning can be enhanced through design-based learning challenges requiring a playful mindset.
Keywords: Playful learning, teaching innovation, creativity, toy design, entrepreneurship, higher education
Artificial Intelligence and Social Computing 2025 : Proceedings of the 16th International Conference on Applied Human Factors and Ergonomics and the Affiliated Conferences, Orlando, Florida, USA, 26-30 July 2025